Alström syndrome – a case report and literature review - Karska-Basta, Izabella; Kubicka-Trząska, Agnieszka; Filemonowicz-Skoczek, Agnieszka; Romanowska-Dixon, Bożena; Kobylarz, Joanna (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Purpose: To report a case of Alström syndrome referred as bilateral macular degeneration. Material and methods: A 52 years old man was diagnosed with an over 30 years history of progressive visual acuity worsening in both eyes, with the presence of night blindness and photophobia. Since childhood the right eye has been positioned in a divergent deviation. General history revealed: high grade obesity, dilated cardiomyopathy with mitral insufficiency, diabetes mellitus type 2, hepatic cirrhosis with elevated serum enzymes, systemic hypertension. Family history: one patient’s brother died at the age of 2 years because of a congenital heart disease, and the second brother was diagnosed for the congenital organic heart disease. The basic ophthalmic examination was performed with additional diagnostic methods including: kinetic visual field examination, Amsler grid test, panel D-15 test, fundus photography, ERG, EOG and VEP. Results: Best corrected visual acuity of both eyes was 0.1. Amsler grid and color vision tests were normal. Visual field revealed concentric contraction in both eyes. The funduscopy showed pale optic discs, atrophic maculopathy, golden appearance of peripheral and midperipheral fundus, coarser pigmentary changes with a „bone-spicule” configuration and arterioral narrowing. The red free pictures demonstrated the atrophy of internal retinal layers and the infrared pictures revealed the atrophy of the external layers of the retina in posterior pole of the fundus. The flash ERG showed reduced amplitude of photopic and scotopic b-wave. The multifocal ERG demonstrated the normal function of the central retina. EOG revealed decreased Arden ratio in both eyes; 1.68 in the right and 1.32 in the left. The pattern VEP revealed the P100 amplitude reduction by 80% and elongation of latency by 120% in the right eye and normal in the left eye. The flash VEP showed normal latency and amplitude reduction by 50% in both eyes. Conclusions: Based on the results of performed tests the diagnosis of Alström syndrome was established. This rare congenital autosomal recessive condition is characterized by progressive cone-rod retinal dystrophy associated with obesity, sensorineural deafness, type 2 diabetes, congenital cardiac insufficiency secondary to dilated cardiomyopathy, systemic hypertension and kidney failure.